Enhancing Literacy Insight Elevating Students Reading Comprehension through Pair Check Strategies - Mikhael Misa; Elisabeth Baintaka; Hesni Neno (Asosiasi Periset Bahasa Sastra Indonesia, 2023)
The pair-check method is a novel instructional approach to enhance students' reading comprehension. The study aimed to examine the impact of applying the pair check method for teaching reading comprehension students at SMPN. The experimental group consisted of 30 students, while in the control group, 30 students received instruction without any specific reading method, relying solely on opening a dictionary. The sample comprised 20 students from class A and B as the sample. The control group was instructed by using reading method and the experimental group was taught by applying pair checks method. The pre-test and post-test scores were compared between the experimental and control groups. The results indicated that the experimental class exhibited significant improvement in both pre- and posttest scores, with a notable increase in the average score from 33.6 in the pretest to 33.32 in the posttest. In addition, the control class, employing traditional teaching methods, exhibited a substantial increase in posttest score, indicating noteworthy progress in learning outcomes. These findings underscore the importance of instructional methods in influencing student outcomes, with the pair-Check method emerging as a practical and effective tool for improving reading comprehension in the educational setting. Further research and analysis are recommended to delve deeper into the statistical significance of these observations and to inform future instructional strategies for optimizing student learning outcomes in the classroom.